Primary Cilia in Pancreatic β- and α-Cells: Time to Revisit the Role of Insulin-Degrading Enzyme - Pablos, Marta; Casanueva-Álvarez, Elena; González-Casimiro, Carlos M.; Merino, Beatriz; Perdomo, Germán; Cózar-Castellano, Irene (Frontiers in Endocrinology, 2022)
The primary cilium is a narrow organelle located at the surface of the cell in contact with the extracellular environment. Once underappreciated, now is thought to efficiently sense external environmental cues and mediate cell-to-cell communication, because many receptors, ion channels, and signaling molecules are highly or differentially expressed in primary cilium. Rare genetic disorders that affect cilia integrity and function, such as Bardet-Biedl syndrome and Alström syndrome, have awake interest in studying the biology of cilium. In this review, we discuss recent evidence suggesting emerg¬ing roles of primary cilium and cilia-mediated signaling path¬ways in the regulation of pancreatic β- and α-cell functions, and its implications in regulating glucose homeostasis.